Mining Beneficial Genes for Salt Tolerance From a Core Collection of Rice Landraces at the Seedling Stage Through Genome-Wide Association Mapping - Wang, Xiaoliang; Li, Jinquan; Sun, Jian; Gu, Shuang; Wang, Jingbo; Su, Chang; Li, Yueting; Ma, Dianrong; Zhao, Minghui; Chen, Wenfu (Frontiers in Plant Science, 2022)
Rice is a salt-sensitive plant. High concentration of salt will hinder the absorption of water and nutrients, and ultimately affect the yield. In this study, we assessed the salt tolerance (ST) of rice at the seedling stage and performed a genome-wide association study (GWAS) based on genotypic data including 2,487,353 single-nucleotide polymorphisms (SNPs) detected in a core collections of rice landraces. Based on the QK model of MLM model, we conducted an association analysis for ST at rice seedling stage. Eight salinity related traits were evaluated under salinity stress (100mM NaCl) and normal conditions in a growth chamber. A total of 65 QTLs significantly associated with ST were identified by GWAS. Six co-localized QTLs were identified. Among them, one co-localized region qTL4 was located on chromosome 6 consisting of 3 QTLs, which can explain 14.38%-17.94% of the phenotypic variation. The qTL4 was located at the highest peak at approximately 28.93Mbp. Based on the local linkage disequilibrium, 94 candidate genes were screened in this region (+/- 500 kb). According to haplotype analysis, qRT-PCR analysis and sequence alignment, it was finally determined that 4 candidate genes (LOC_Os06g47720, LOC_Os06g47820, LOC_Os06g47850, LOC_Os06g47970) were related to ST. The results provide useful candidate genes for marker assisted selection for ST in the rice molecular breeding programs.